2019
DOI: 10.1002/chem.201901731
|View full text |Cite
|
Sign up to set email alerts
|

Through‐Space Spin Coupling in a Silver(II) Porphyrin Dimer upon Stepwise Oxidations: AgII⋅⋅⋅AgII, AgII⋅⋅⋅AgIII, and AgIII⋅⋅⋅AgIIIMetallophilic Interactions

Abstract: Metallophilic interactions between closed‐shell metal ions are becoming a popular tool for a variety of applications related to high‐end materials. Heavier d8 transition‐metal ions are also considered to have a closed shell and can be involved in such interactions. There is no systematic investigation so far to estimate the structure and energy characteristics of metallophilic interactions in AgII/AgII (d9/d9), AgIII/AgIII (d8/d8), and mixed‐valent AgII/AgIII (d9/d8) complexes, which have been demonstrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 164 publications
1
9
0
Order By: Relevance
“…The term aurophilicity was established by Schmidbaur to describe attractive interactions between Au I centers, relyingo n earlier findings and empirical evidence. [1][2][3][4][5][6] Since then, substantial efforts have been made to understandt he nature of such interactions, [7][8][9][10][11][12] furthere xtended to other M···M contacts, such as argentophilicity. [13] In spite of the relatively low stabilization energy,i nt he rank of hydrogen bonds, numerous examples in which metallophilic interactions efficiently modifyc hemical and physicalp roperties of metal-based compounds and materials have been described.…”
mentioning
confidence: 99%
“…The term aurophilicity was established by Schmidbaur to describe attractive interactions between Au I centers, relyingo n earlier findings and empirical evidence. [1][2][3][4][5][6] Since then, substantial efforts have been made to understandt he nature of such interactions, [7][8][9][10][11][12] furthere xtended to other M···M contacts, such as argentophilicity. [13] In spite of the relatively low stabilization energy,i nt he rank of hydrogen bonds, numerous examples in which metallophilic interactions efficiently modifyc hemical and physicalp roperties of metal-based compounds and materials have been described.…”
mentioning
confidence: 99%
“… a Center-to-center distance between the centroids of the N 4 unit. b Interplanar angle, defined as the angle between the mean 23-atom plane (or 24-atom plane in the case of Ag-3 ) of the two macrocycles. c Slip angle (α), defined as the average angle between the vector normal to the N 4 plane and the Ag···Ag vector. d Lateral shift between the two Ag centers, defined as (sin α)­(Ct···Ct distance). e Electronic density at the BCP in atomic units. f Laplacian of the electronic density in atomic units. g Electron delocalization index between Ag centers (i.e., average number of electrons shared between the two Ag ions) from Bader analysis. h Wiberg bond index from NBO analysis. i [SbF 6 ] − salt, CCDC 1536021. j Data reproduced from ref . k [PF 6 ] − salt, CCDC 1536020. l Center-to-center distance between mean 24-atom planes. m Angle between the vector normal to the mean 24-atom plane and the Ct···Ct vector. n Calculated for the DFT-optimized geometry. o Data reproduced from ref . p CCDC 1907233. q CCDC 1907234. r CCDC 1907235. …”
Section: Resultsmentioning
confidence: 99%
“…Stepwise oxidation resulted in shorter Ag···Ag distances: 3.61 Å for Ag­(II)/Ag­(II), 3.53 Å for mixed-valent Ag­(II)/Ag­(III), and 3.45 Å for Ag­(III)/Ag­(III). A Bader analysis revealed that the strength of the Ag···Ag interaction increases with the oxidation state . Because β-unsubstituted silver corroles are authentic Ag­(III) species, rather than Ag­(II) complexes with a noninnocent ligand [i.e., a Ag­(II) corrole radical cation], as in the case of copper corroles, silver corroles offer an ideal platform to observe Ag­(III)···Ag­(III) argentophilic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The value of electron density 1 and the sign of Laplacian distribution r 2 1(r) at bond critical point (BCP) are closely related to bonding strength and nature of interaction respectively in any pair of interacting atoms. [46] The values of several relevant parameters for selected bond pairs are summarized in Table 1. The strength of such interactions were also determined according to the method proposed by Espinosa et al [41] and Vener et al [42] Based on the crystal structure data and the aforementioned guideline of QTAIM analysis, we found that in complex 3, each Mg atom binds with only two P atoms, whereas each Ca atom binds with three P atoms in complex 4 (Figure 8).…”
Section: Molecular Modelingmentioning
confidence: 99%